Kirschner Wire Breakage during Removal Requiring Retrieval - Kai Yuen Wong; Rosalind Mole; Patrick Gillespie (Case Reports in Surgery)
Kirschner wires (K-wires) are widely used for fixation of fractures and dislocations in the hand as they are readily available, reliable, and cost-effective. Complication rates of up to 18% have been reported. However, K-wire breakage during removal is rare. We present one such case illustrating a simple technique for retrieval. A 35-year-old male presented with a distal phalanx fracture of his right middle finger. This open fracture was treated with K-wire fixation. Postoperatively, he developed a pin site infection with associated finger swelling. The K-wire broke during removal with the proximal piece completely retained in his middle phalanx. To minimise risk of osteomyelitis, the K-wire was removed with a novel surgical technique. He had full return of hand function. Intraoperative K-wire breakage has a reported rate of 0.1%. In our case, there was no obvious cause of breakage and the patient denied postoperative trauma. On the other hand, pin site infections are much more common with reported rates of up to 7% in the hand or wrist. K-wire fixation is a simple method for bony stabilisation but can be a demanding procedure with complications often overlooked. It is important to be aware of the potential sequelae.